(untitled) (Global Journal of Science Frontier Research, 2018)
A significantly large number of earlier works on the subject of fractional calculus give the interesting account of the theory and applications of fractional calculus operators in many different areas of mathematical analysis (such as integral equations, special functions, the summation of series, etc.) paper is to study and develop the Saigo give the images of the product of two multivariable Gimel multivariable polynomials in Saigo-Saigo-Maeda operators, multivariable Gimel large number of new and known theorems involving Riemann fractional integral operators and several special functions.